2001
DOI: 10.1016/s0304-3959(00)00461-9
|View full text |Cite
|
Sign up to set email alerts
|

TMJ disorders and myogenic facial pain: a discriminative analysis using the McGill Pain Questionnaire

Abstract: Our aim was to assess the discriminative capacity of the McGill Pain Questionnaire (MPQ) in patients with temporomandibular joint (TMJ) disorders or with myogenous facial pain (MP). The MPQ was administered to 57 TMJ and 28 MP patients who were also asked to assess the level of pain using the Visual Analog Scale (VAS). Weighted MPQ item scores, subscale Pain Rating Indexes (PRI), total PRI and the number of words chosen were calculated. Mean scores were tested for significant differences (Student's t-test), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 13 publications
3
7
0
1
Order By: Relevance
“…This is consistent with findings indicating that the preference of MPQ pain descriptors is associated with pain chronicity [67] as well as pain type and localization [68]. In contrast to other TMD sufferers, patients with primarily myogenic facial pain and headache choose more affective descriptors and rate the pain as more intensive [24,52,67,68]. The higher psychosomatic burden reflected by the CL scores underpins the picture of subjects who display various pain locations of similar intensity and a number of accessory complaints.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with findings indicating that the preference of MPQ pain descriptors is associated with pain chronicity [67] as well as pain type and localization [68]. In contrast to other TMD sufferers, patients with primarily myogenic facial pain and headache choose more affective descriptors and rate the pain as more intensive [24,52,67,68]. The higher psychosomatic burden reflected by the CL scores underpins the picture of subjects who display various pain locations of similar intensity and a number of accessory complaints.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, TMJ pain, as a clinical sign, is a common finding in FM patients, also reported in a previous study, 6 but with a lower incidence than muscle pain. These findings indicated that MMP is an important factor in the coexistence of FM and TMD as reported by Leblebici et al 8 Besides, considering that TMD is classically characterized by (1) TMJ pain and/or masticatory muscles pain, (2) TMJ sound, and (3) alteration in the mandibular movements, 41,42 we found that 68.4% of the subjects presented 2 or 3 signs of TMD at the same time. Our results suggest that many FM patients have clinical characteristics of TMD, which can render FM management difficult.…”
Section: Discussionsupporting
confidence: 80%
“…The basic difference between SOM and traditional vector quantization techniques is that SOM is a completely data‐driven, unsupervised learning method. Details relative to the application of this methodology to MPQ data have been previously described 25 …”
Section: Methodsmentioning
confidence: 99%
“…It has been found that the MPQ satisfactorily discriminates between reversible and irreversible tooth nerve damage, 19 trigeminal neuralgia and atypical facial pain, 20 cluster headache and migraine, 21 and between various types of facial pain 22,23 . More recently, the MPQ consistently discriminated between craniomandibular joint pain and facial pain as a somatoform disorder, 24 and between temporomandibular joint (TMJ) pain and myogenic facial pain 25 …”
mentioning
confidence: 99%